2020
DOI: 10.1007/s10549-020-05627-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of epithelial-mesenchymal transition-related markers and phenotypes during breast cancer progression

Abstract: Purpose The study aimed to investigate expression of epithelial-to-mesenchymal transition (EMT)-related proteins and phenotypes during breast cancer progression and to relate this to patient outcome. Methods Protein expression patterns of E-cadherin, N-cadherin, twist, and vimentin were examined by immunohistochemistry on formalin-fixed paraffin-embedded samples from primary tumors (PTs) (n = 419), synchronous lymph node metastases (LNMs) (n = 131) and recurrences (n = 34) from patients included in an observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…This observation was further confirmed at mRNA level, using a clinical cohort of breast tumors. Furthermore, in agreement with our results, vimentin-positive EMT was associated with more aggressive TNBC tumors 41 .…”
Section: Discussionsupporting
confidence: 92%
“…This observation was further confirmed at mRNA level, using a clinical cohort of breast tumors. Furthermore, in agreement with our results, vimentin-positive EMT was associated with more aggressive TNBC tumors 41 .…”
Section: Discussionsupporting
confidence: 92%
“…The majority (7 cases) were EMT-V (58.3%). This distribution is comparable to a recent tissue microarray immunohistochemical study by Jørgensen et al (2020) 83 where breast cancers which expressed both loss of epithelial and gain of mesenchymal markers (classified as “mesenchymal” in their study and equivalent to EMT-CV in our study) were almost equal in number as those that had absence of both epithelial and mesenchymal markers (classified as “negative” in their study and equivalent to EMT-C in our study). Their study also showed that tumours with retention of epithelial markers but gain of mesenchymal markers (classified as “partial’ in their study and equivalent to EMT-V in our study) was the larger majority.…”
Section: Results and Analysissupporting
confidence: 91%
“…The results of this study demonstrated a moderate increase in the expression of fibronectin protein in B. burgdorferi infected MCF 10A cells, but there was a detectable increase in the expression level of fibronectin, vimentin, and Twist1/2 protein and a statistically significant increase in activated MMP9 level at 72 h post B. burgdorferi infection in the MDA-MB-231 cells. In good agreement with our findings, a study that investigated the expression of some EMT markers during breast cancer progression also demonstrated vimentin expression positivity associated with aggressive tumors such as the triple-negative subtype [ 37 ]. Similarly, H. pylori significantly upregulates vimentin in the gastric cancer cell lines as well as increases the expression of MMP-7 [ 38 ].…”
Section: Discussionsupporting
confidence: 91%